IMPROVING STUDENTS’ ACHIEVEMENT IN CREATING BROCHURE BY USING MEDIA OF ANIMATION VIDEO TO THE TENTH GRADE OF MIPA 1 SMA NEGERI 1 TONGAS PROBOLINGGO - Surya Dewi Fatmawati (JIRA: Jurnal Inovasi dan Riset Akademik, 2021)
This classroom action research was intended to improve the tenth grade students’ writing achievement in creating brochure at SMAN I Tongas Probolinggo by applying media of animation video. The respondents of this classroom Action research (CAR) were class XMIPA 1 that was determined purposively. The class XMIPA 1 were chosen as the subjects of this research because the class had more complicated problem dealing with writing and their average score in writing was the lowest among three existing classes that was 70.2 in the first semester. This CAR consisted of two cycles, in which each cycle covered four main stages including: the planning of the action, the implementation of the action, classroom observation. Meanwhile, the supporting data were gathered from interview and documentation. The result of the average score of the writing test in the first cycle was M=70,75 that was classified in the fair category. This result did not achieved the standard average score requirement in this research that was M≥75. Besides, based on the classroom observation that was done in the first cycle, it was found that the students’ involvement in the process of writing activities was 45%. Therefore, the actions were proceeded to the second cycle by revising the first action cycle such as: optimalizing the students’ participation in the process of writing activities, giving enough clues about the present tense ‘command sentences’, brochure and the way to apply media of animation video to the students. The results of the average score of the writing test in the second cycle was better M=75.86 that was classified in the good category. Besides, the students’ involvement in the writing process improved from 45% in the first cycle up to 84,6% in the second cycle. It means that both the students’ writing test and the students’ involvement in the writing process improved in the second cycle and fulfilled the target of this research. Based on the results, it could be concluded that the use of video animation media could improve the tenth st grade students’ writing achievement at SMAN I Tongas Probolinggo in two cycles. Then it is suggested to The English teacher to apply media of animation video as the alternative way of English teaching technique, especially in teaching writing a brochure. This is expected to facilitate and to help the students collaborate and share knowledge and experiences with their classmate to solve the writing problems.